Metal matrix composites : materials, manufacturing and engineering - Davim, J. Paulo (Advanced composites., 2014)
Metal Matrix Composites (MMC's) have found an increased use in various industries duetotheir special mechanical and physical properties. They are a composite material with at least two constituent parts, one being a metal and are made by dispersing a reinforcing material into a metal matrix. The markets are: telecommunications, automotive, power semiconductor, opto-electronics, military and aerospace, heavy transportation, space systems and satellites, medical, and industrial lighting. Applications within these markets include microwave, micro-electronic packaging, laser diode, HB-LED's, and advanced radar.